The flowering of ecology : Maria Sibylla Merian's caterpillar book - Etheridge, A. Kay, 1954- (Emergence of natural history, 2021)
"The Flowering of Ecology presents an English translation of Maria Sybilla Merian's 1679 'caterpillar' book, Der Raupen wunderbare Verwandelung und sonderbare Blumen-Nahrung. Her processes in making the book and an analysis of its scientific content are presented in a historical context. Merian raised insects for five decades, recording the food plants, behavior and ecology of roughly 300 species. Her most influential invention was an "ecological" composition, where the metamorphic cycles of insects (usually moths and butterflies) were arrayed around plants that served as food for the caterpillars. Kay Etheridge analyses the 1679 caterpillar book from the viewpoint of a biologist, arguing that that Merian's study of insect interactions with plants, the first of its kind, was a formative contribution to natural history"--